Estimation of above-ground biomass of a tropical forest in Northern Borneo using high-resolution satellite image - Phua, Mui How; Ling, Zia-Yiing; Wong, Wilson Vun Chiong; Alexius Korom; Berhaman Ahmad; Normah Awang Besar; Satoshi Tsuyuki; Keiko Ioki; Keigo Hoshimoto; Yasumasa Hirata; Hideki Saito; Gen Takao (Kangwon National University, Chunchon, Korea, 2014)
Estimating above-ground biomass is important in establishing an applicable methodology of Measurement, Reporting and Verification (MRV) System for Reducing Emissions from Deforestation and Forest Degradation-Plus (REDD+). We developed an estimation model of diameter at breast height (DBH) from IKONOS-2 image that led to above-ground biomass estimation (AGB). The IKONOS image was preprocessed with dark object subtraction and topographic effect correction prior to watershed segmentation for tree crown delineation. Compared to the field observation, the overall segmentation accuracy was 64%. Crown detection percent had a strong negative correlation to tree density. In addition, satellite-based crown area had the highest correlation with the field measured DBH. We then developed the DBH allometric model that explained 74% of the data variance. In average, the estimated DBH was very similar to the measured DBH as well as for AGB. Overall, this method can potentially be applied to estimate AGB over a relatively large and remote tropical forest in Northern Borneo.